Thermal Performance Assessment of the Kaligung K3 New Image Passenger Coach Using OTTV and CLTD - M. Aditya Bintang Septian Nugraha; Althesa Androva; Muhamad Safi'i (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
The Kaligung K3 New Image train is equipped with an air conditioning system to maintain passenger thermal comfort. Passenger comfort can be disturbed by heat from ambient temperature, the train envelope, passengers, lighting, and electronic equipment, thereby increasing the cooling load, the value of which is not yet known. This research aims to calculate heat transfer as an indicator of the thermal performance of the train envelope using the OTTV method and to find out the total cooling load of the passenger room when the train stops at Semarang Poncol Station during the day, during the train boarding process, from factors internal, external, ventilation, and infiltration, including the addition of a safety factor of 10% using the CLTD method. Data were obtained through field measurements, training technical documents, and thermal comfort regulations. The results show an OTTV value of 28.01 W/m² (less than or equal to 35 W/m², SNI 6389:2020) and a total cooling load of 35,237.69 kcal/h (<36,000 kcal/h), indicating that the cooling capacity is sufficient to handle the cooling load. This research concludes that the OTTV and CLTD approach methods are effective for analyzing heat transfer and cooling loads on trains and for evaluating existing cooling capacity.